ANALISIS KEMAMPUAN PEMAHAMAN KONSEP DAN MINAT BELAJAR MATEMATIKA MATERI PERKALIAN SISWA KELAS III UPT SD NEGERI 117 GRESIK - Putri Firdatun Nisa’; Arissona Dia Indah Sari (Jurnal Al-Fatih, 2022)
This research was to analysis of the ability to understand the concept and interest in learning mathematics multiplication theory in third grade of UPT SD Negeri 117 Gresik. The purpose is to describe how much students are able to understand the concept of multiplication and their interest in learning mathematics. The research is a qualitative research that used descriptive methods. The data used in this research were obtained using test and questionnaire. The is all third grade students of UPT SD Negeri 117 Gresik. The results showed in very good category there are 5%, in good category there are 36%, and in enough category there are 59%. Interest in learning mathematics is 32% in very high category and 68% in enough category. It can be concluded overall the ability to understand the concept in good category with percentage 70,8% and the interest in learning mathematics overall in enough category with percentage 74,5%.Concept Understanding Ability, Interests, Multiplication Theory.